The Extent to Which Computational Thinking Skills Are Included in Programming Units within Digital Skills Courses for Primary Schools in Saudi Arabia - Al-Rasheed, Fatimah Abdulaziz; Al-Fahid, Mai Fahid (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the computational thinking skills to be included in the programming units of the digital skills courses for the primary school, to identify the extent to which they are included in these units. In addition, it aims to present a proposal for the inclusion of computational thinking skills in the programming units of the digital skills courses for the primary stage. To achieve the objectives of the study, the descriptive approach in the method of content analysis has been adopted. The study community included all programming units in the digital skills courses of the 5th grade in the 2nd semester, and the 6th grade in the 1st and 2nd semesters in Saudi Arabia. It included the student book of the academic year 1440-1441H, (3 books) included (5 programming units). The study tool was the content analysis card. The most important results were as follows: To include computational thinking skills in programming units within Digital Skills Courses of Primary grade with (47.9%) with a high inclusion score. To include the algorithmic thinking skill in the first place, with the inclusion of (56.6%), followed by the decomposition skill, with the inclusion of (51.2%), then the skill of abstraction, with the inclusion of (47.3%), and finally the skill of generalization and patterns, with the inclusion (36.4%). The study provided a proposal for developing the inclusion of computational thinking skills in programming units with digital skills courses in the light of the results of the analysis. The study recommended making use of the proposal in designing some projects in the course that would develop computational thinking skills and directing primary school students to do technical projects that enhance the development of computational thinking skills and show its role in solving problems.